2020
DOI: 10.1177/1534734620943021
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Diabetic Foot Ulcers With Necrotizing Fasciitis in the Lower Leg Using the STAGE Principles: A Report of 9 Cases With a Literature Review

Abstract: Diabetic foot ulcers (DFUs) combined with necrotizing fasciitis (NF) has rapid onset, involves a wide range of lesions, is difficult to treat, and has a high mortality rate. It has become a clinically critical disease. DFU patients are at high risk for NF. The STAGE principles guide surgical intervention in the treatment of DFU wounds and emphasizes that “based on anatomical layers, the management focuses on blood supply and includes layer-by-layer incision to the infected area, maintenance of effective wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Without prompt treatment with appropriate antibiotics and/or debridement of infected tissues, patients may develop toxic shock syndrome, leading to multiple organ failure and mortality. However, the result of bacterial susceptibility is not only lagging but also has a high false-negative rate, therefore, it has limited guiding significance for clinical antibiotic application [ 29 ]. Additionally, before the bacterial culture results are available, the choice of antibiotics is mainly based on the doctor’s experience and the severity of the infection [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Without prompt treatment with appropriate antibiotics and/or debridement of infected tissues, patients may develop toxic shock syndrome, leading to multiple organ failure and mortality. However, the result of bacterial susceptibility is not only lagging but also has a high false-negative rate, therefore, it has limited guiding significance for clinical antibiotic application [ 29 ]. Additionally, before the bacterial culture results are available, the choice of antibiotics is mainly based on the doctor’s experience and the severity of the infection [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings parallel literature reports: studies that distinguish patients according to microbiological profile did not find differences in terms of clinical outcomes. 30 The anaesthesiologist approach, centered on less invasive methods more suitable to such complicated patients ended in no postoperative complications and a little need for pain-killer drugs. 31 Even better than expected compared to the data reported in the literature in these difficult cases.…”
Section: Discussionmentioning
confidence: 99%
“…These findings parallel literature reports: studies that distinguish patients according to microbiological profile did not find differences in terms of clinical outcomes. 30…”
Section: Discussionmentioning
confidence: 99%
“…Yin et al 10 have demonstrated that autologous stromal vascular fraction cells plus platelet-rich plasma improve the healing of chronic lowerextremity ulcerations in subjects with diabetes mellitus. Zhu et al 11 have found that preconditioning local vibrations might help towards the prevention of foot ulcers in high-risk subjects.The issue is completed by case reports [12][13][14][15] and letters. This journal is unswerving in its mission to advance our knowledge of wound healing.…”
mentioning
confidence: 99%
“…The issue is completed by case reports [12][13][14][15] and letters. This journal is unswerving in its mission to advance our knowledge of wound healing.…”
mentioning
confidence: 99%